Preventing industrial accidents : reappraising H.W. Heinrich--more than triangles and dominoes - Busch, Carsten (New York : Routledge, 2021)
"Herbert William Heinrich has been one of the most influential safety pioneers. His work from the 1930s/1940s affects much of what is done in safety today - for better and worse. Heinrich's work is debated and heavily critiqued by some, while others defend it with zeal. Interestingly, few people who discuss the ideas have ever read Heinrich's work or looked into the backgrounds, most do so based on hearsay, secondary sources or mere opinion. One reason for this is that Heinrich's work has been out of print for decades, it is notoriously hard to find, and quality biographical information is hard to get. Based on some serious 'safety archaeology', which gave access to many of Heinrich's original papers, books and rather rich biographical information, this book aims to fill this gap. The book deals with the life and work of Heinrich, the context he worked in, and looks into his influences and his legacy. The book defines the main themes in Heinrich's work and discusses these paying attention to their origins, the developments that came from them, interpretations and attributions, and the critique that they may have attracted over the years. This includes well-known ideas and metaphor as the accident triangle, the accident sequence (dominos), hidden cost of accidents, the human element and management responsibility. This book is the first to deal with the work and legacy of Heinrich as a whole, based on a unique richness of material, and approaching the matter from several (new) angles. The book also reflects regularly on Heinrich's relevance for today's safety science and practice"--
OCLC-licensed vendor bibliographic record.
Keywords: Industrial safety; Heinrich, H. W. -- 1886-1962.; BUSINESS & ECONOMICS / Management; TECHNOLOGY / Industrial Health & Safety; BUSINESS & ECONOMICS / Insurance / Risk Assessment & Management